ESÎRÜDDİN EL-EBHERÎ’NİN MUĞALATA’YA (SAFSATA) BAKIŞI - Kamil Kömürcü (İslami İlimler Dergisi)
Sophisme, according to al-Abharî, is a syllogism consisting of incorrect propositions. These propositions are fallacy and deceptive. One approaches these syllogisms to deceive the other people consciously or unconsciously. One protects himself/herself from the erroneouses, learning these typical syllogisms. According to al-Abharî, the fallacy in a syllogism occurs either from the matter of this syllogism or its form. Sometimes, the fallacy occurs from both the matter and the form. The fallacy originating from its form arises from violating the conditions that generate valid conclusion. Al-Abharî evaluates these typical fallacy under six titles in the varied books. The fallacy originating from its matter results from the utterance of syllogism or its meaning. Al-Abharî investigating two fallacy regarding the utterance, expresses fifteen fallacies regarding the meaning, in addition to three fallacies resembling these. Al-Abharî presents twenty six fallacies regarding the utterance and the meaning.